The Impact of Covid-19 on Financial Performance and Share Price on Cigarette Companies Listed on Indonesia Stock Exchange (IDX) - Nita Rislawati; Nardi Nardi; Asmadhini Handayani Rahmah; Fitriansyah Fitriansyah (International Journal of Quantitative Research and Modeling, 2022)
This study aims to determine and analyze differences in financial performance and stock prices before and after Covid-19 incigarette companies. Financial performance in this study is measured using three ratios namely Return on Asset (ROA), OperatingProfit Margin (OPM) and Net Profit Margin (NPM). The data used in this study is secondary data from the type of financialstatements of Cigarette Companies from the Indonesia Stock Exchange (IDX) website and the official website of cigarettecompanies, and the sampling method used is sampling census because the samples used in this study are the financial statements ofthe entire population of Cigarette Companies registered with the IDX in the third quarter of 2019 to the fourth quarter of 2020. Theanalysis method in this study is the wilcoxon test using SPSS 26. Based on the results of research obtained show Return on Assets(ROA), Operating Profit Margin (OPM) and stock price showed no significant differences before and after Covid-19. Net ProfitMargin (NPM) shows significant differences before and after Covid-19. To find out and analyze the state of cigarette companies inthe Covid-19 pandemic and also as a consideration for investors and business people in policy making